Посох всевластия - Корепанова Наталья (Издательские решения, 2021)
Экземпляры: УКП (20211124) / Инвентарный номер: АП20210077 / Цена: / Сис.шифр: 84(2) / Авт.знак: К 66 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4